Meperkenalkan Budaya Lokal Dengan Menguasai Bahasa Inggris - Sugianto, Sugianto; Tawali, Tawali; Hasby, Muhammad Asrul; Muhlisin, Muhammad (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The program is aimed at empowering the Penelando community members which is unified in Tourism awareness arisen community at the Sagik Mateng village. The team of lecturers from English study department of Mandalika University of Education conducted a program by providing training and practical guidance of English conversation to fifteen members of the culture Community of Penelando Jerowaru, East Lombok. Through this program, the team of lecturers empowered the community members by trasfering English language skills. The four crucial steps: planning, coordination, execution, and evaluation of method were used in the implementing the program . The mastery of the English language skills can be used to introduce the local culture to the tourists who come to visit the village. Mastering English enables the local community to interact with the international world. As well as allowing themto actively participate in sustainable tourism promotion. Through English mastery, the community may enrich multicultural education, as well as developing local arts and cultures tobe enjoyed by the global audiences. The English language skills mastered by the community are expected to preserve local identity, ensuring that cultural values and traditions remain alive in the context of globalization. By the end of the program, the team were successfully integrated English as a strategic tool to preserve and promote the unique local culture of Sagik Mateng village on the international stage through visiting tourists.